The comparison of cytotoxicity of the anticancer drugs doxorubicin and ellipticine to human neuroblastoma cells - Poljaková, Jitka; Eckschlager, Tomáš; Hřebačková, Jana; Hraběta, Jan; Stiborová, Marie (Interdisciplinary toxicology, 2008)
Ellipticine is an antineoplastic agent, whose mode of action is based mainly on DNA intercalation, inhibition of topoisomerase II and formation of covalent DNA adducts mediated by cytochromes P450 and peroxidases. Here, the cytotoxicity of ellipticine to human neuroblastoma derived cell lines IMR-32 and UKF-NB-4 was investigated. Treatment of neuroblastoma cells with ellipticine was compared with that of these cancer cells with doxorubicin. The toxicity of ellipticine was essentially the same as that of doxorubicin to UKF-NB-4 cells, but doxorubicin is much more effective to inhibit the growth of the IMR-32 cell line than ellipticine. Hypoxic conditions used for the cell cultivation resulted in a decrease in ellipticine and/or doxorubicin toxicity to IMR-32 and UKF-NB-4 neuroblastoma cells.
Keywords: anticancer drug; cytotoxicity; human neuroblastoma cells; doxorubicin; ellipticine